Risperidone-induced Premature Ventricular Complexes in Psychosis: A Case Report - Javed A Siddiqui; Shazia F Qureshi; Yousef BA Shawosh (Indian Journal of Private Psychiatry)
Atypical antipsychotics are known to cause cardiovascular side effects, such as prolonging the QTc interval due to blockade of the potassium repolarization channels, and hence they predispose to ventricular arrhythmias, like premature ventricular complexes (PVCs). Here, we report a case of a male schizophrenic patient who is complaining of palpitations and feeling clinically as well as symptomatically troublesome PVCs associated with risperidone. We consider that PVCs may have been generated by risperidone, with his stressful mental condition, and subsided after withholding it.